Protocol for a cohort study of adolescent mental health service users with a nested cluster randomised controlled trial to assess the clinical and cost-effectiveness of managed transition in improving transitions from child to adult mental health services (the MILESTONE study). Issue 10 (16th October 2017) - Singh, Swaran P; Tuomainen, Helena; Girolamo, Giovanni de; Maras, Athanasios; Santosh, Paramala; McNicholas, Fiona; Schulze, Ulrike; Purper-Ouakil, Diane; Tremmery, Sabine; Franić, Tomislav; Madan, Jason; Paul, Moli; et al.
Abstract : Introduction: Disruption of care during transition from child and adolescent mental health services (CAMHS) to adult mental health services may adversely affect the health and well-being of service users. The MILESTONE (Managing the Link and Strengthening Transition from Child to Adult Mental Healthcare) study evaluates the longitudinal course and outcomes of adolescents approaching the transition boundary (TB) of their CAMHS and determines the effectiveness of the model of managed transition in improving outcomes, compared with usual care. Methods and analysis: This is a cohort study with a nested cluster randomised controlled trial. Recruited CAMHS have been randomised to provide either (1) managed transition using the Transition Readiness and Appropriateness Measure score summary as a decision aid, or (2) usual care for young people reaching the TB. Participants are young people within 1 year of reaching the TB of their CAMHS in eight European countries; one parent/carer and a CAMHS clinician for each recruited young person; and adult mental health clinician or other community-based care provider, if young person transitions. The primary outcome is Health of the Nation Outcome Scale for Children and Adolescents (HoNOSCA) measuring health and social functioning at 15 months postintervention. The secondary outcomes include mental health, quality of life, transition experience and healthcare usage assessed at 9, 15 and 24 months postintervention. With a mean cluster size of 21, a total of 840 participants randomised in a 1:2 intervention to control are required, providing 89% power to detect a difference in HoNOSCA score of 0.30 SD. The addition of 210 recruits for the cohort study ensures sufficient power for studying predictors, resulting in 1050 participants and an approximate 1:3 randomisation. Ethics and dissemination: The study protocol was approved by the UK National Research Ethics Service (15/WM/0052) and equivalent ethics boards in participating countries. Results will be reported at conferences, in peer-reviewed publications and to all relevant stakeholder groups. Trial registration number: ISRCTN83240263 ; NCT03013595 (pre-results).